2019
DOI: 10.1111/dth.12894
|View full text |Cite
|
Sign up to set email alerts
|

Generalized hypertrichosis due to secukinumab in a patient with moderate psoriasis: A case of serendipity or zemblanity?

Abstract: After 4 months of therapy with secukinumab, a 67‐year‐old man with moderate psoriasis developed generalized hypertrichosis, along with PASI 90. The patient denied any drug intake, apart from secukinumab, nor applications of any creams. Moreover, this event did not really bother the patient, thus the therapy was not discontinued and the hypertrichosis is persisting as psoriasis' control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…9 In recent years, hypertrichosis has been reported in anecdotal cases or series cases. 1,2,10 Rongioletti et al, 2 reported on a patient with erythrodermic psoriasis who was treated with secukinumab. After 6 months of therapy, the patient noticed that his scalp hair was becoming darker over the entire scalp with a diffuse increase in hair density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In recent years, hypertrichosis has been reported in anecdotal cases or series cases. 1,2,10 Rongioletti et al, 2 reported on a patient with erythrodermic psoriasis who was treated with secukinumab. After 6 months of therapy, the patient noticed that his scalp hair was becoming darker over the entire scalp with a diffuse increase in hair density.…”
Section: Discussionmentioning
confidence: 99%
“…It can be congenital or acquired and localized or generalized. 1 Hypertrichosis has been associated with various prescription drugs such as corticosteroids, cyclosporine, retinoids, antibiotics, antihypertensive drugs, psoralen, phenytoin, diazoxide, minoxidil, and latanoprost. 2,3 In recent years, biological therapy seems to be associated with hypertrichosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess hair growth was not bothersome to the fifth and was identified in a routine visit 20 months after starting therapy 4 . Three patients developed generalized hypertrichosis most visible on the trunk and extremities 1,4 . Two had increased hair on the scalp with repigmentation of gray hair 2,3 .…”
Section: Patient Age/sex Treatment Indication Il‐17 Inhibitor Psorias...mentioning
confidence: 99%
“…All five reported patients to date were male with a median age of 62 (range 39-85) and moderate-to-severe psoriasis at baseline (Table 1). [1][2][3][4] Two patients had erythrodermic psoriasis, two had severe plaque psoriasis, and one had moderate recalcitrant psoriasis. Specific IL-17A inhibitors included secukinumab in four patients and ixekizumab in one.…”
mentioning
confidence: 99%